Railways and Spanish economic growth in the late 19th century - Gómez Mendoza, A; Gómez Mendoza, Antonio (1981)
﻿ The object of this thesis is to examine the contribution of Spanish railways to accelerated economic growth in the period. 1855-1913. Although it has not been estimated, there is reason to believe that there was some growth in the period before the 20th century but, from all accounts, it was constrained by an inefficient, highly seasonal and costly road transportation system. The contribution of railways will be assessed in three ways, First, by estimating the cost of the non-construction of the railway network through an estimate of the social savings. This estimate suggested that the contribution cf railways accounted for 12 per cent of Spain's national income in 1878 and 23 per cent in 1912. I/hen the full employment assumption embodied in these calculations is released, social savings diminished to the 'plausible' level of 7.5 per cent in 1878. Second, as consumers of iron and steel, railways had little linkage effects on the iron industry because they imported the bulk of the iron required to lay down the network. The implications of an alternative policy which protected the local iron industry from the begiiining of railway expansion are treated at length. Railways had, on the other hand, important feedback effects upon the domestic coal production and one fifth of the coal mined in Spain was consumed by railways. Thirdly, connections between railways and the spread of the market reveal that they were a fundamental factor in the integration of the home market. Railways carried increasing volumes of grain, flour, wine and coal consumed in Spain.